Hybrid Plasmonic Modes for Enhanced Refractive Index Sensing - Bereket Dalga Dana; Ji Boyu; Jingquan Lin; Longnan Li; Alemayehu Nana Koya; Wei Li (Advanced Sensor Research, 2023)
Abstract Compared to single nanoparticles, strongly coupled plasmonic nanoparticles provide attractive advantages owing to their ability to exhibit multiple resonances with unique spectral features and higher local field intensity. These enhanced plasmonic properties of coupled metal nanoparticles have been used for various applications including realization of strong light‐matter interaction, photocatalysis, and sensing. In this article, the basic physics of hybrid plasmonic modes in coupled metallic nanodimers is reviewed and their potentials for refractive index sensing are assessed. In particular, the spectral line shapes of various modes of hybrid plasmons including bonding and antibonding modes in symmetric nanodimers, Fano resonances in asymmetric nanodimers, charge transfer plasmons in linked nanoparticle dimers, hybrid plasmon modes in nanoshells, gap modes in particle‐on‐mirror configurations, and hybrid magnetoplasmonic modes in heterodimers are overviewed. Beyond the dimeric nanosystems, the potentials of surface lattice resonances in periodic nanoparticle arrays for sensing applications are also showcased. Finally, based on the critical assessment of the recent research on coupled plasmonic modes, the outlook on the future prospects of hybrid plasmon‐based refractometric sensing are discussed. Given their tunable resonances and ultranarrow spectral features, coupled metal nanoparticles are expected to play key roles in developing precise plasmonic nanodevices with extreme sensitivity.